Suspected Compartment Syndrome and Rhabdomyolysis after “Pseudoephedrine” Use: A Case Report - Eric Medrano; Jake Goliver (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Acute compartment syndrome and rhabdomyolysis are two life threatening diagnoses that cannot be missed in the emergency room. The increased pressure in the closed compartments of extremities can eventually lead to loss of peripheral pulses, decreased tissue perfusion, and ultimately muscle necrosis. This breakdown of muscle byproducts will ultimately lead to kidney damage and rhabdomyolysis. Although the most common cause of compartment syndromes are secondary orthopedic causes such as lower extremity fractures there are known documented toxicological causes. (1,2) Pseudoephedrine, a sympathomimetic amine, is commonly used in the treatment of nasal congestion. Its primary mechanism directly acts on the adrenergic receptor system which stimulates release of stored norepinephrine from neurons. Its alpha-adrenergic effect is believed to be the cause of vasoconstriction in the body (3) Clinically, intoxication from sympathomimetic drugs have produced toxidromes with prominent features such as tachycardia, hypertension, hyperthermia, agitation, and delirium. However, it is incredibly rare to see an association with pseudoephedrine overdose and rhabdomyolysis and compartment syndrome. There are documented cases where sympathomimetic drugs have been associated with compartment syndrome (2,4,5) This case of a 29-year-old male with suspected pseudoephedrine abuse highlights the need for consideration of rhabdomyolysis and compartment syndrome being a possible complication from pseudoephedrine overdose.